2022
DOI: 10.1097/md.0000000000031153
|View full text |Cite
|
Sign up to set email alerts
|

A survey of caregiver burden for stroke survivors in non-teaching hospitals in Western China

Abstract: The social factors that moderate stroke caregiver burden have been found to be culture- and gender-specific. We examined the factors that influence the social support and self-efficacy of caregivers of stroke survivors and the burden of caregiving in China. To determine the caregiver burden of stroke survivors, their social support, and their self-efficacy. A total of 328 stroke survivors and their caregivers were recruited from 4 tertiary medical centers to participate in this cross-sectional study. The socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In our study, 67% (284) of primary caregivers experienced a burden from care, with a high proportion experiencing a mild to moderate burden (61.1%) followed by a high burden (5.9%). The finding is consistent with that of studies conducted in China (Cao et al, 2022) and India (Menon et al, 2017) that revealed 67.1 and 65% of the participants were experiencing varying degrees of burden, respectively. But lower than the study conducted in Nigeria (Akosile et al, 2018), where 96.7% of caregivers reported having a high burden.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, 67% (284) of primary caregivers experienced a burden from care, with a high proportion experiencing a mild to moderate burden (61.1%) followed by a high burden (5.9%). The finding is consistent with that of studies conducted in China (Cao et al, 2022) and India (Menon et al, 2017) that revealed 67.1 and 65% of the participants were experiencing varying degrees of burden, respectively. But lower than the study conducted in Nigeria (Akosile et al, 2018), where 96.7% of caregivers reported having a high burden.…”
Section: Discussionsupporting
confidence: 91%
“…The interplay between caregivers’ self-rated health and their burden is another recurrent theme [ 30 , 35 , 37 ] converging on the notion that caregivers with better self-rated health tend to experience a lower burden. Conversely, poorer self-rated health intensifies the burden experienced by caregivers, leading to a cyclic relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The type of health insurance does not substantially reduce caregiver burden due to limited reimbursement content. Low insurance reimbursement rates contribute to the financial strain experienced by caregivers [ 35 ]. Prolonged hospitalization leads to increased financial burden on caregivers due to expenses associated with hospital visits and increased susceptibility to infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation